ANALISIS KINERJA KEUANGAN PT. SANSHIRO HARAPAN MAKMUR DENGAN MENGGUNAKAN METODE DU PONT SYSTEM - Syam, Alim; Lasmana, Andy (Jurnal Akunida, 2016)
This research is aims to knowledge financial performace of company if it is analyzed using methode Du Pont System. Financial ratio analysis with Du Pont System analysis aproach is analysis to show the relationship between Net Profit Margin (NPM), asset circulation or Total Assets Turn Over (TATO) and Return On Investment (ROI) to determine company Return On Equity (ROE). Type research is descriptive. Data source includes primary and secondary data. Data collection technique is documentation and interview. The result showed that the performance of PT. Sanshiro Harapan Makmur, seen in Return On Equity (ROE) and Return On Investment (ROI) tended to decline during the periode 2010-2014. Return On Equity (ROE) is caused by several things, among them is inefficiency in the total cost increases and not balanced with the Earning After Tax (EAT), Net Profit Margin (NPM) that fluctuating for five years.Keywords : Net Profit Margin (NPM), Total Assets Turn Over (TATO), Return On Investment (ROI), Return On Equity (ROE)